Length but not transverse diameter of the excision specimen for high-grade cervical intraepithelial neoplasia (CIN 2–3) is a predictor of pregnancy outcome. Issue 5 (September 2016) - Liverani, Carlo A.; Di Giuseppe, Jacopo; Clemente, Nicolò; Delli Carpini, Giovanni; Monti, Ermelinda; Fanetti, Fabiana; Bolis, Giorgio; Ciavattini, Andrea
Abstract : The objective of this study was to analyze the impact of cone characteristics (depth, transverse diameter, and volume) on subsequent pregnancies after the loop electrosurgical excision procedure (LEEP) for cervical intraepithelial neoplasia (CIN 2–3). Pregnancy outcomes (preterm birth, gestational age at birth, mode of delivery, and birth weight) of 501 women with singleton gestations and no previous preterm birth or history of late miscarriage, who had previously undergone a single LEEP for CIN 2–3, were retrospectively analyzed with respect to length, transverse diameter, and volume of the excision specimen. The overall incidence of preterm birth was 2.4%. The rate of preterm birth in women with length greater than 20 mm or volume greater than 2.5 cm 3 was significantly higher than that in women with length between 15 and 19 mm (15.6 vs. 3.9%, P =0.02) or women with volume between 2.0 and 2.4 cm 3 (5.8 vs. 1.6%, P =0.04). A linear inverse correlation ( r =−0.3, P <0.001) between gestational age at birth and length, but not volume ( r =0.0, P =0.9) or transverse diameter ( r =0.2, P <0.0001), emerged. The mode of delivery was not affected by cone characteristics. Length, but not transverse diameter and volume, of the excised specimen seems to be related to a lower gestational age at birth. When excisions are performed under strict colposcopic guidance, with a correct modulation of cone length, the risk for preterm birth and cesarean delivery in subsequent pregnancies is not increased.